ANALYSIS OF THE ABSORBTION OF EUROPEAN FUNDS FOR TOURISM DEVELOPMENT - Marioara Ilea; Diana Reaboi (Agricultura, 2017)
By analyzing the European funds in the tourism field through the Regional Operational Program 2007-2013, was following the rate of realization and grade of absorption. In order to obtain the results used in this study, the analysis of data collected from the Annual Implementation Reports provided by the Ministry of Regional Development, Public Administration and European Funds was used as a research method. After analyzing the data gathered from these reports it was found that the degree of absorption of the projects from the period under study in this program was not maximized, due to the poor preparation of the bodies responsible for the implementation and poor education of potential beneficiaries. For some areas of this axis, the results were positive beyond the proposed objectives. This analysis results in the need to improve the implementation of the next ROP program, but also that people are more interested in becoming beneficiaries of European funds in the coming years.